Real-life Applications with Membrane Computing - Zhang, Gexiang; Pérez-Jiménez, Mario J.; Gheorghe, Marian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book thoroughly investigates the underlying theoretical basis of membrane computing models, and reveals their latest applications. In addition, to date there have been no illustrative case studies or complex real-life applications that capitalize on the full potential of the sophisticated membrane systems computational apparatus; gaps that this book remedies. By studying various complex applications - including engineering optimization, power systems fault diagnosis, mobile robot controller design, and complex biological systems involving data modeling and process interactions - the book also extends the capabilities of membrane systems models with features such as formal veriﬁcation techniques, evolutionary approaches, and fuzzy reasoning methods. As such, the book offers a comprehensive and up-to-date guide for all researchers, PhDs and undergraduate students in the fields of computer science, engineering and the bio-sciences who are interested in the applications of naturalcomputing models.
Membrane Computing - Key Concepts and Deﬁnitions -- Fundamentals of Evolutionary Computation -- Membrane Algorithms -- Engineering Optimization with Membrane Algorithms -- Electric Power System Fault Diagnosis with Membrane Systems -- Robot Control with Membrane Systems -- Data Modeling with Membrane Systems: Applications to Real Ecosystems.
Keywords: Computational intelligence; Artificial intelligence; Dynamics; Nonlinear theories; Computational Intelligence; Artificial Intelligence; Applied Dynamical Systems